2017
DOI: 10.1002/term.2384
|View full text |Cite
|
Sign up to set email alerts
|

Surgical repair of annulus defect with biomimetic multilamellar nano/microfibrous scaffold in a porcine model

Abstract: Annulus defect is associated with reherniation and disc degeneration after discectomy; currently there is no effective treatment that addresses this problem. The annulus is a hierarchical lamellar structure, where each lamella consists of aligned collagen fibres, which are parallel and tilted at 30° to the spinal axis. In this study, a biomimetic biodegradable scaffold consisting of multilamellar nano/microfibres, sharing nanotopography and microporosity similar to the native lamellar structure, was assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…The nano/microfibres aligned as native collagen tissue of AF. These results show that these scaffolds can form and integrate collagen fibers ( Kang et al, 2018 ).…”
Section: Tissue Engineering Strategiesmentioning
confidence: 73%
See 1 more Smart Citation
“…The nano/microfibres aligned as native collagen tissue of AF. These results show that these scaffolds can form and integrate collagen fibers ( Kang et al, 2018 ).…”
Section: Tissue Engineering Strategiesmentioning
confidence: 73%
“…The results showed that, in addition to numerous dense collagen fibers in the aligned scaffolds, the fibers were arranged in the same direction as the scaffold ( Gluais et al, 2019 ). Kang et al (2018) combined electrospinning and 3D printing techniques to fabricate a biomimetic biodegradable scaffold that consisted of multi-lamella nano/microfibers. Each lamella contained one layer of aligned electrospun nanofibers and one layer of supporting 3D printed microfibers on each side, which were all aligned in the same direction, and the angle of the fibers between adjacent layers was 60°.…”
Section: Tissue Engineering Strategiesmentioning
confidence: 99%
“…111 Another group employed multilamellar nanofibrous/microfibrous scaffolds seeded with bmMSCs to repair AF defects in a porcine model. 112 The scaffolds were sealed into the AF lesion using fascia and medical glue, followed by suture fixation. After 12 weeks, cell-free and cell-seeded scaffold repair groups demonstrated no significant difference in terms of disc height index, T1-r value, T2 value, or repair thickness.…”
Section: Mobilizing Cellular Players For Annulus Fibrosus Repairmentioning
confidence: 99%
“…Rat AF puncture Increased histological grade scores and enhanced ECM formation/8 weeks (Zhang, Yu, Zhao, et al, 2018) Hyaluronic acid hydrogel defect and retard the development of degeneration (Ledet, Jeshuran, Glennon, et al, 2009). To mimic the lamellar structure, multilamellar nano/microfibers was developed and have been found to integrate well with the surrounding AF tissue and reduce disc degeneration in a porcine model (Kang, Li, Xi, et al, 2016). The abovementioned animal studies indicate that filling of the defect and bridging with the existing tissues can be achieved in AF repair; nevertheless, fibrillary, lamellar organisation, and excellent integration with the surrounding AF tissue are the looming challenges in long-term repair.…”
Section: Cell-freementioning
confidence: 99%